Evaluation of the retinal hemodynamics in patients with primary open angle glaucoma and differing nocturnal blood pressure profiles - Yusof, Firdaus; Cheng, Richard; Espahbodi, Nadia; Khuu, Lee-Anne; Buys, Yvonne M; Trope, Graham; Hudson, Christopher; Flanagan, John G (2014)
Purpose: To evaluate the retinal hemodynamic response to normoxic hypercapnia among patients with primary open angle glaucoma (POAG) and differing nocturnal blood pressure (NBP) profiles, using Doppler spectral-domain optical coherence tomography (SD-OCT). Methods: Doppler SD-OCT retinal blood flow (RBF) measurement was acquired using the circum-papillary double circular scan protocol of the RTVue system (Optovue Inc., Freemont, CA). The sample consisted of 17 healthy controls (group mean age 62±7 years; group mean NBP dip 14±8%); 17 POAG with normal NBP dip (age 66±9 years; NBP dip 11±5%), termed “dippers”; and 16 POAG with high NBP dip (age 64±7 years; NBP dip 24±5%), “over-dippers”. The NBP dip magnitude was calculated by taking the difference between mean arterial pressure (MAP) during the day and night while awake and asleep, respectively. Automated gas blender (RespiractTM, Thornhill Research Inc., Toronto) was used to stably provoke normoxic hypercapnia (15% increase in the end-tidal carbon dioxide partial pressure relative to homeostatic baseline). Six Doppler SDOCT RBF scans were acquired, during baseline and also during normoxic hypercapnia. RBF parameters were calculated and ANOVA was used to compare values between groups (p<0.05). Results: Total RBF at baseline was significantly different between the groups with controls being the highest (37.1±4.4mL/min), and over-dippers the lowest (29.6±9.0mL/min). Venous area showed significant differences at baseline between the groups with the lowest value in the over-dipper group, and the highest in the control group (39.9±7.0(x10-3)mm, and 46.6±6.6x(10-3)mm, respectively). Velocity was not significantly different between groups (p=0.27) at baseline. Breathing normoxic hypercapnia provoked an increase in flow that was significantly lower in the over-dipper group (1.0±8.6mL/min) and highest in the controls (8.2±10.8mL/min). Change in velocity was significantly different (p=0.02) between the groups, being highest in the control group (2.4±3.3mm/s) and lowest in the over-dipper group (-0.6±3.1mm/s). Venous area change was not significantly different between groups. Conclusions: Patients with POAG who exhibited an exaggerated nocturnal reduction in MAP also demonstrated lower baseline RBF values and an impeded retinal vascular response to normoxic hypercapnia, indicating greater vascular dysregulation in this group.